The mental disorders patients’ right human denying - Pereira, Maria Alice; Furegato, Antonia Regina Ferreira (Rev Rene, 2000)
The present study was developed with patients that experience long psychiatric hospitalization periods. The purpose was to identify thoughts and knowledges about madness and its consequences to their lives, evidencing the denial of their human right. Authors used the life history technique to interview four psychiatric unit women hospitalized. The theoretical methodological procedures were enriched with constituted observation and the projective technique use (free drawing and drawing according a specific theme). Authors used thematic analysis to work with data, what enabled them to identify social representations that constituted an organized system of thoughts in psychopathologic theories. Based on concrete experiences, patients elaborated theories that showed their difficult lifes as mental disorder women. They translated their drama as women who had a madness experience and were submitted to long period hospitalizations.